ANALISIS SUMBERDAYA TERUNJUK BATU ANDESIT MENGGUNAKAN METODE CROSS SECTION DAN METODE TRIANGULAR DI PT. BINTANG SUMATERA PASIFIK, KECAMATAN PANGKALAN KOTO BARU, KABUPATEN LIMA PULUH KOTA, PROVINSI SUMATERA BARAT - Refky Adi Nata; Rizky Edra Suryadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT. Bintang Sumatera Pasifik is a mining company that operates andesite in Nagari Manggilang Pangkalan, Lima Puluh Kota, West Sumatra. Geographically located at coordinates 100⁰ 44 ' 46,3 "East longitude and the 00⁰ 01’09,8" South latitude. With an area of 6 Ha Mining Permit. This study will count the stones resources using the method of cross section with the distance between the section 20 m, helped by software Rockworks to make pieces of the section as well as create a Block model of sediment stones, and methods triangular grouping who assisted with Autodesk land Desktop software to find out the coordinates of the point of the outcrop. Data processing of the results obtained with andesite resources using the method of cross section of 11.826.129,6 tons (ρ = 2,7 ton/m3) and by using the method of triangular grouping obtained resources of 6.529.096,512 tons (ρ = 2,7 ton/m3) with the lower elevation 156 mdpl and limits the upper elevation 277 mdpl.Keywords: Cross Section, Triangular Grouping, Resources, Andesite,  Autodesk Land Desktop